Development of low cost vehicle dynamic data acquisition device using GPS, IMU and OBD integrated system - Mohamad Amilhasan, Shafie (2016)
Malaysian automotive industry was develop to the level of improvement of the comfort of riding to the users. The researched for the comfort of riding is needed the data to improve the development of the vehicle component design. However, the technique to acquire data used by one of Malaysian's automotive company is only by subjective testing. This is because the investment needed to access the proper DAQs for testing is very costly. The solution for this problem is the development of low cost vehicle dynamics DAQ system. The development of this device is the purpose of this thesis. The device is developed with the U AV evaluation board which is available in the market. The developed device was developed with low cost and capable of acquire 6 DoF data with 500 Hz. sampling time, GPS data, altitude data, 3-axis magnetometer and engine parameter.